RARE-24. The use of novelin vitro models to study adamantinomatous craniopharyngioma disease biology and drug response. (3rd June 2022) - Trudeau, Tammy; Prince, Eric; Chatain, Oscar; Chee, Keanu; Jackson, Eric; Limbrick, David; Naftel, Robert; Feldstein, Neil; Grant, Gerald; Ginn, Kevin; Niazi, Toba; Smith, Amy; et al.
Abstract: BACKGROUND: Challenges around the design and investigation of cell culture models of adamantinomatous craniopharyngioma (ACP) have arisen from the cellular heterogeneity of these tumors, with populations that harbor disparate requirements in culture. Novel approaches to in vitro modeling of ACP are needed. METHODS: Intraoperatively collected tumor specimens were mechanically digested and plated under conditions tailored to the cell population of interest. ACP tumor-derived fibroblasts and epithelial cells were isolated using serum-containing and keratinocyte-specific media respectively. ACP-derived epithelial cells were immortalized via SV40 virus transfection and puromycin treatment for stable cell-line generation. Cell line validation included immunofluorescence with markers appropriate for the cell population of interest. RNA sequencing of cell lines was compared to ACP transcriptome reference data. Cell typing was conducted using short tandem repeat sequencing. RESULTS: ACP fibroblasts and ACP epithelial cells maintained spindle-like and cobblestone morphologies respectively, even after 4 passages. Immunofluorescence staining confirmed high levels of Vimentin expression in ACP-derived fibroblasts, and panCK and B-catenin in ACP-derived epithelial cells. Point mutation in exon 3 of the CTNNB1 gene was identified in ACP-derived epithelial cells. CONCLUSION: Initial limits related to cell line development in ACP may be addressed through the isolation and culture-specific ACP cell populations. This experience demonstrates the maintenance of validated markers of the cell populations of interest ex vivo . While preliminary, such cell lines offer promise as tools for the identification and study of potential therapeutic vulnerabilities in ACP.